METHODOLOGY FOR TEACHING BIOLOGY IN ACADEMIC LYCEUMS - Nodira Toyqulovna Fayziyeva (European Science Publishing, 2024)
The article proposes one of the important tasks that will help biology teachers in lyceums choose the most rational, convenient, modern, visual, easy to understand and master educational material method in biology. The importance of other related sciences, such as philosophy, chemistry, physics, ecology, genetics, psychology, in teaching biology in lyceums is shown. As you know, evolutionary theory lays the foundation for all modern biology. For a long time, evolutionism has retained many questions that have not yet been fully studied and there are no clear answers to them; in addition, evolutionism can be traced not only in biology, but also in many other sciences.
Keywords: biology, methodology, textbook, pedagogy, philosophy, psychology, chemistry.